Overexpression of galactinol synthase 1 from Solanum commersonii (ScGolS1) confers freezing tolerance in transgenic potato - Feiyan He; Jianfei Xu; Yinqiao Jian; Shaoguang Duan; Jun Hu; Liping Jin; Guangcun Li (Horticultural Plant Journal, 2023)
Potato (Solanum tuberosum L.) is the fourth largest food crop in the world. Low temperatures cause serious damage to potato plants every year, and freezing tolerance has become a hot spot in potato research. Galactinol synthase (GolS) is a key enzyme in the synthesis of raffinose family oligosaccharides (RFOs), and plays an important role in the response of plants to abiotic stress. In this study, the ScGolS1 gene from Solanum commersonii was cloned and introduced into the S. tuberosum cultivars ‘Atlantic’ and ‘Desiree’ via Agrobacterium-mediated transformation. Phenotyping assays showed that overexpression of ScGolS1 could significantly improve freezing tolerance in transgenic potato plants. Further physiological and biochemical experiments showed that the transgenic lines had lower relative conductivity, malondialdehyde content, and 3,3′-diaminobenzidine staining and a higher plant survival rate compared with wild type (WT) under cold stress. Moreover, the C-repeat binding factors (CBF1, CBF2 and CBF3), the downstream cold-responsive genes COR413 and COR47, and the ethylene-responsive factor (ERF) transcription factor genes ERF3, ERF4 and ERF6, which function in the ethylene signaling pathway, were all induced by freezing treatment and expressed at higher levels in the ScGolS1 overexpression lines compared with WT. Besides, the expression of some genes such as MIPS, STS and RS from the RFO metabolic pathway was up-regulated under cold stress, resulting in changes in the content of some soluble sugars. This indicated that ScGolS1 overexpression altered the sugar composition and enhanced freezing tolerance in transgenic potato by inducing the ethylene and CBF signaling pathways. These results provided theoretical support and genetic resources for freezing tolerance breeding in potato.